Pengaruh Debt Equity Ratio, Current Ratio dan Return On Asset Terhadap Price Book Value (Studi Kasus Perusahaan Sub Sektor Transportasi Yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2019-2023) - Zaumil Zifa Titaningrum; Eka kurnia Patmasari; Ageng Prasetyo (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2025)
This study aims to determine the effect of Capital Structure, Liquidity, and Profitability on Firm Value in the transportation sub-sector listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Capital Structure is proxied by the Debt to Equity Ratio (DER), Liquidity is proxied by the Current Ratio (CR), Profitability is proxied by the Return on Assets (ROA), and Firm Value is proxied by the Price to Book Value (PBV). The study was conducted on 30 transportation sub-sector companies during the 2019–2023 period, selected using a purposive sampling method with a secondary quantitative approach. The analytical technique used in this research is Multiple Regression Analysis. The results show that, partially, Capital Structure has a significant positive effect on Firm Value, while Liquidity and Profitability have no effect on Firm Value. However, simultaneously, Capital Structure, Liquidity, and Profitability together influence Firm Value.